Perjuangan Mahasiswi Gitar Klasik pada Jenjang Pendidikan Sarjana Musik di Indonesia - Andre Indrawan; Dara Benita Titihalawa (Institut Seni Indonesia Denpasar, 2022)
The population of guitar students in the Bachelor of Music Study Program, Faculty of Performing Arts, Institut Seni Indonesia Yogyakarta, is dominated by male students. Purpose: This study aims to uncover women's efforts in gaining learning achievement in the context of guitar studies at the Indonesian higher education level. Research Method: This study uses qualitative research methods with interview instruments. However, in the analysis of some preliminary data using a quantitative approach. Result and discussion: Results and Interviews with four female alums and four active students provided information about their effort in pursuing Bachelor's studies with a classical guitar major. The analysis includes motivation, learning process, gender, and expectations. Implication: This study concluded that all subjects were not affected by the dominance of men in the guitar student population at ISI Yogyakarta. For them, gender does not affect the quality of learning outcomes; instead, perseverance and enthusiasm for learning play an important role.